Peran Surat Kabar Bandera Islam Dalam Perjuangan Khilafah 1924-1927 - Waginugroho, Septian Anto (PT. Student Rihlah Indonesia, 2023)
The aim of this study was to investigate the role of Bandera Islam newspaper in the Caliphate movement from 1924 to 1927. The current study was conducted by using a historical approach in four stages: searching of historical sources (heuristics), critics, interpretation, and historical writing (historiography). Bandera Islam was a newspaper in Melayu language published by an Islamic organization movement in Hindia Belanda (Indonesia) called Sarekat Islam. At that time, newspaper publishing was a well-known method used by organizational movements to socialize their thoughts to the public. Bandera Islam had been published since 1924 until 1927, along with the period in which Sarekat Islam involved in the Caliphate movement. Therefore, many articles written by Sarekat Islam activists were found in Bandera Islam.